2012
DOI: 10.1179/2046905512y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of acute lower respiratory tract infection in South African children

Abstract: ALRTIs in children <5 years impose a heavy economic burden on families and the South African public health-care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…A recent study conducted in South Africa found that 87.4% of children under 5 years of age had at least one episode of bronchiolitis or pneumonia in an 18-month period. Of these children, 10.5% had two ARI episodes, and 1.7% had three episodes 12. Bates et al13 reported that 49.5% of infants who participated in their study in Nepal had bronchiolitis or pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study conducted in South Africa found that 87.4% of children under 5 years of age had at least one episode of bronchiolitis or pneumonia in an 18-month period. Of these children, 10.5% had two ARI episodes, and 1.7% had three episodes 12. Bates et al13 reported that 49.5% of infants who participated in their study in Nepal had bronchiolitis or pneumonia.…”
Section: Discussionmentioning
confidence: 96%
“…Since the additional disease-specific costs are not included in these estimates, for all diseases we inflated CHOICE estimates by 25% to account for the cost of disease-specific drugs, diagnostics, and procedures. This fraction is based on the fraction reported in a recent South African pneumonia costing study [48]. Household costs were assumed to be equivalent to the percentage of total health expenditure which is out-of-pocket, based on estimates from the WHO Global Health Expenditure Database [49].…”
Section: Health Services Costsmentioning
confidence: 99%
“…Eleven treatment cost studies, which were not part of Hib vaccine economic evaluations, were identified (Table VII). Six low-income countries (Fiji, India, Kenya, Pakistan, Vietnam, and Zambia 5359 ) and 5 middle-income countries (Columbia, Chile, Brazil, South Africa, and Uruguay 60–62 ) were represented. Sample sizes for estimating patient-specific costs ranged from 56 patients in 1 of the 2 Indian studies to 980 patients in the study from Vietnam.…”
Section: Country Groupsmentioning
confidence: 99%